Why Do Buyers Pay Different Prices for Comparable Products? Evidence from the Housing Market - Ralph Siebert; Michael J. Seiler (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We focus on the housing market and examine why nonlocal home buyers (NLBs) pay 15 percent more for houses than local home buyers (LBs). We estimate a housing demand model that returns heterogeneous willingness to pay parameters for housing attributes. Our results show that NLBs are willing to pay more for specific housing attributes, especially for house size and school quality. We also find that gratification and reward arguments, and imperfect price information explain the price differential to a large extent. Search cost and house age arguments have an adverse effect on NLBs' house spending.
Keywords: L13; L49; L63; 330; heterogeneous preferences; housing market; imperfect information on price distributions; school quality; search costs